2013
DOI: 10.1523/jneurosci.0400-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activity in Valuation Regions while Thinking about the Future Predicts Individual Discount Rates

Abstract: People vary widely in how much they discount delayed rewards, yet little is known about the sources of these differences. Here we demonstrate that neural activity in ventromedial prefrontal cortex (VMPFC) and ventral striatum (VS) when human subjects are asked to merely think about the future-specifically, to judge the subjective length of future time intervals-predicts delay discounting. High discounters showed lower activity for longer time delays, while low discounters showed the opposite pattern. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 41 publications
6
53
0
1
Order By: Relevance
“…Neural responses during time perception predict discounting rates, such that steeper discounting rates are associated with increased neural activity when judging short, compared to long, delays. 26 The ability to delay gratification and maintain goal-directed behavior in the face of cravings to smoke is critical to maintain smoking abstinence. These higher order cognitive functions rely on accurate time perception.…”
Section: Introductionmentioning
confidence: 99%
“…Neural responses during time perception predict discounting rates, such that steeper discounting rates are associated with increased neural activity when judging short, compared to long, delays. 26 The ability to delay gratification and maintain goal-directed behavior in the face of cravings to smoke is critical to maintain smoking abstinence. These higher order cognitive functions rely on accurate time perception.…”
Section: Introductionmentioning
confidence: 99%
“…In order to compare the differences in reaction time, we split participants into two groups of assessors and locomotors according to relative strength of regulatory mode orientations [32]. Assessment and locomotion scores were first converted to normally distributed z-scores, respectively.…”
Section: Behavioral Resultsmentioning
confidence: 99%
“…Results showed that assessors did not spend more time in making decisions than locomotors did (T = 1.083, df = 72, p = 0.282). Following cooper et al [32], we used two different approaches to examine the link between regulatory mode and delay discounting. First, we computed the correlations between two regulatory mode scores and delay discounting.…”
Section: Behavioral Resultsmentioning
confidence: 99%
“…Impulsive choice uniquely relies on delay processing, and interval timing processes have been implicated as playing an important role in impulsive choice (Baumann & Odum, 2012;Cooper, Kable, Kim, & Zauberman, 2013;Cui, 2011;Lucci, 2013;Marshall et al, 2014;Takahashi, 2005;Takahashi, Oono, & Radford, 2008;Wittmann & Paulus, 2008;Zauberman, Kim, Malkoc, & Bettman, 2009). The dorsal striatum (DS) is a key target for timing processes as it has been proposed to function as a "supramodal timer" (Coull, Cheng, & Meck, 2011) that is involved in encoding temporal durations (Coull & Nobre, 2008;Matell, Meck, & Nicolelis, 2003;Meck, 2006;Meck, Penney, & Pouthas, 2008).…”
Section: Domain-specific Brain Mechanismsmentioning
confidence: 99%